Mitigating target degradation in sputtering manganite thin films. (February 2018) - Dildar, I.M.; Boltje, D.B.; Hesselberth, M.B.S.; Beekman, C.; Aarts, J.
Abstract: In this paper, we address the issue of aging of oxide sputtering targets, using the example of La0.7 Ca0.3 MnO3 (LCMO), a material which is quite sensitive to the amount of oxygen. After prolonged use we find that the morphology of the films becomes poor: holes appear, the size of the steps between terraces becomes larger, the roughness increases, and electrical conductance in the metallic state at temperatures below the metal-insulator transition becomes smaller. We have performed experiments on reactive sputtering with water vapor in order to reverse their degradation. We discuss the growth and properties of films of LCMO on flat SrTiO3 substrates before and after the target treatment. We study both the morphological and structural changes in these films as well as the transport properties. The results indicate that a correct concentration of oxygen in the targets is important, and that a deficiency can be compensated by the water treatment, thus increasing the usable life time of targets. Highlights: A frequently used La0.7 Ca0.3 MnO3 target start growing rough films. The target was found to be oxygen deficient. As a remedy, oxygen is added in form of water vapors during reactive sputtering. The grown films showed improved morphology after the treatement. Structural and transport properties of films improved in quality as well.